Analisis perbandingan rencana strategi pada perusahaan asuransi di Indonesia - Faraz, Laode; Hakiki, Mohamad Fahmi; Rifqi, Muhammad (Maliki Interdisciplinary Journal, 2023)
This article discusses the importance of strategy and planning in developing insurance company businesses in Indonesia. This research uses a qualitative approach through a literature review and research data sources come from various literature, such as books, scientific journals, magazines, official websites and documents. This research looks at the strategic plans of three insurance companies in Indonesia: PT Prudential Life Assurance, PT Asuransi Bintang Tbk., and PT Asuransi Dayin Mitra Tbk. By considering the financial, environmental, technological and human resources sectors, this analysis was carried out. The results show that Prudential Indonesia has a different approach to managing business operations and achieving long-term goals. Prudential Indonesia also excels in the application of technology and human resource development. This comparative analysis shows that strategy and business planning are essential for insurance companies to remain competitive in a competitive market. To meet market needs and demonstrate its commitment to social responsibility, every company must reconsider its strategy. In conclusion, this article emphasizes that insurance companies must have a clear and well-planned strategy to be able to compete in a competitive market. In addition, companies must consider the use of technology and human resource development to improve customer service and meet market needs.